Cytology of the healthy canine and feline ocular surface: comparison between cytobrush and impression technique. (24th January 2017) - Perazzi, Anna; Bonsembiante, Federico; Gelain, Maria Elena; Patruno, Marco; Di Iorio, Enzo; Migliorati, Angelo; Iacopetti, Ilaria
Abstract : Background: Impression cytology (IC) is a noninvasive technique in which filters are used to sample superficial layers of ocular epithelium. Objectives: The aim of this study was to compare cytology specimens obtained by IC and cytobrush from healthy canine and feline eyes. Methods: Dogs and cats were prospectively sampled using polytetrafluorethylene filters on the right eye, and cytobrush on the left eye. Wright–Giemsa‐stained specimens were evaluated by 2 observers. Cellularity, preservation, and morphology of cells and presence of goblet and inflammatory cells were scored with a 4‐grade scale. Inter‐observer agreement and effects of topical anesthesia were analyzed. Results: In 20 canine IC samples, 10 showed good cellularity (score 2–3) and 13 good preservation. Superficial epithelial cells (SEC) were present in 13/20 of IC, while basal‐intermediate cells (BIC) were seen in 14/20. In 6/20 and 7/20, goblet and inflammatory cells were noted, respectively. In 20 cats, 15 of IC showed good cellularity and 14 good preservation, and SEC were present in 16/20 of IC and BIC in 17/20. In 13/20 and 3/20 cats, goblet cells and inflammatory cells were noted, respectively. Canine cytobrush specimens appeared well preserved (9/20) and had good cellularity (8/20). In feline cytobrush specimens, good preservation and cellularity were observed in 16/20 and 14/20, respectively. In both species, all cell types were present without a clear separation. There was moderate to fair agreement about cellular morphology in IC between observers. Specimens obtained with and without anesthesia were comparable. Conclusion: Impression cytology allowed collection of samples with maintained cytoarchitecture, while cytoplasmatic and nuclear details were often difficult to evaluate.